Synergistic stabilisation of emulsions by blends of dairy and soluble pea proteins: Contribution of the interfacial composition. (December 2019) - Hinderink, Emma B.A.; Münch, Katharina; Sagis, Leonard; Schroën, Karin; Berton-Carabin, Claire C.
Abstract: Proteins from animal and plant sources are known to be able to physically stabilise emulsions, whereas much less is known about emulsions prepared with blends of proteins of different origin. Here we use blends of pea protein isolate (PPI) with whey protein isolate (WPI) or with sodium caseinate (SC) to physically stabilise emulsions prepared by high pressure homogenisation. For both the blends and the individual proteins, droplet size, emulsion stability, surface load and interfacial compositions were determined. The d 3, 2 and surface load (measured over a concentration range 0.2–1.6 wt% protein in the starting aqueous solution) were the lowest for SC- and WPI-stabilised emulsions, and the highest for PPI-stabilised emulsions, whereas emulsions stabilised by the blends (1:1 ratio) had intermediate d 3, 2 values and surface loads. PPI- and SC-stabilised emulsions showed some physical destabilisation (e.g., flocculation and coalescence, respectively) over 14 days of storage, whereas the WPI-PPI or SC-PPI blends formed emulsions that remained stable, suggesting synergistic effects.When used in blends, both dairy and plant proteins adsorbed at the oil-water interface, but compositional rearrangements at the interface occurred within days. More specifically, whey proteins were able to partly displace pea proteins from the interface, which were themselves able to displace SC. However, such a displacement was only possible when the displacing protein was present in sufficiently high excess. Such considerations are usually not taken into account in food emulsion formulation, even though they are very relevant, as the interfacial layer protects emulsions droplets against physical destabilisation. Graphical abstract: Image 1 Highlights: Blending pea proteins with dairy proteins leads to enhanced emulsion stability. Both proteins co-exist at the interface in plant-dairy protein stabilised emulsions. Changes in interfacial composition occur during storage. A given protein needs to be in excess to cause interfacial displacement.